Managing plant architecture for quality apples - Ahmed, N; Kumar, Dinesh; Lal, Shiv; Ahmed, N (Indian Horticulture, 2019)
The plant architectural energy can be efficiently utilized into development of quality fruits. The 80-90% of fruits obtained by this system are of A grade. The technique involves nothing special as it is a management technology. Thus, it is an advanced high-tech management technique that enable farmers to get quality apples without any special expenditure.